Service-dominant logic perspective on technology-based business incubator - Eka Yuliana; Utomo Sarjono Putro; Pri Hermawan; Astri Ghina (Cogent Business & Management, 2024)
AbstractThis research article examines the implementation of service-dominant logic in technology-based business incubators, specifically focusing on Bandung Techno Park in Indonesia. The research examines the connection between service providers and clients, the function of technology-based business incubators in assisting enterprises, and the consequences of transitioning from a focus on products to a focus on services. This study offers an extensive literature analysis on technology-based business incubators, goods-dominant logic, and service-dominant logic. Additionally, it analyzes the business process structure and services provided by Bandung Techno Park. The study highlights the significance of comprehending service-dominant logic principles while evaluating and improving services in technology-based business incubators. Furthermore, it emphasizes the importance of collaborations between universities and industries, the transition to more participatory innovation models, and the involvement of service-dominant logic in generating value. The article recommends doing further research in this field, namely with larger sample sizes and longitudinal investigations.